Characterization and antimicrobial activity of silver nanoparticles, biosynthesized using Bacillus species - Ghiuță, Ioana; Cristea, Daniel; Croitoru, Cǎtǎlin; Kost, Joseph; Wenkert, Rodica; Vyrides, Ioannis; Anayiotos, Andreas; Munteanu, Daniel (My University, 2018)
In this work, the biosynthesis of silver nanoparticles, using AgNO3 as a precursor, by two Bacillus species, namely Bacillus amyloliquefaciens and Bacillus subtillis, is reported. After the synthesis stages, the absorbance of the brown nanoparticle colloidal solutions was assessed by UV–vis spectrophotometry, which showed the peak absorbance values at 418 nm and 414 nm, corresponding to surface plasmon resonance of silver nanoparticles. The EDX, SEM and DLS analyses confirmed the formation of spherical silver nanoparticles with an average diameter smaller than 140 nm. XRD confirmed the presence of face-centered cubic silver crystals, with the highest intensity peak at 2θ = 38.12°, which corresponds to the (111) diffraction planes. The antibacterial activity after 24 h of incubation was observed against gram negative bacteria: Escherichia coli, Pseudomonas aeruginosa, Salmonella, as well as gram positive: Staphylococcus aureus, Streptococcus pyogenes. Furthermore, the antifungal activity was assessed against Candida albicans. The inhibition zone was clearly observed on the plates containing silver nanoparticles, either standalone or in combination with antibiotics, thus showing their potentiating antibacterial effect.
Keywords: Bacillus amyloliquefaciens; Bacillus subtillis; Biosynthesis; Silver nanoparticles